(3GdeMGSHI GdMchejIs - (3eMeO aVd(B, (3eSYOs; (3NGdO QGZH GdNWjH(B, s ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj(B,s, 2009)
(3JYQja GdeMGSHI GdMchejI h GdedGeM GdQFjSjI dgG , GdejGOF GdCSGSjI aj GdeMGSHI GdMchejI h eYGjjQgG , GdefXeGJ GdOhdjI GdegJeI HGdeMGSHI GdMchejI , GdehGRfI GdYGeI ddOhdI , EYOGO GdehGRfI GdYGeI aj GdeedcI GdCQOfjI GdgGTejI hI JfajPgG , gjcd GdfXGe GdeMGSHj HGdhMOGJ GdMchejI , GdeYGdLI GdeMGSHjI ddYedjGJ GdeGdjI GdMchejI , GdJbGQjQ GdOhQjI h GdMSGHGJ GdNJGejI HGdhMOGJ GdMchejI , GdQbGHI Ydi JfajP GdejRGfjI , GdYdGbGJ Hjf GdeMGSHI GdbhejI h fXQjI GdGbJUGO GdJLejYj h GNjQG fXGe GdeMGSHI GdbhejIs
(3eQGLY U(B.347s
Keywords: (3GdeMGSHI GdMchejIs; (3JObjb GdMSGHGJ GdMchejIs